Artificial Humans in Modern Life: Opportunities and Challenges for Humans - Suryanto, Totok (Indonesian Journal of Social Science Research, 2025)
This article examines the role and impact of artificial humans or artificial intelligence (AI) in the context of modern life, focusing on the opportunities and challenges posed to humans. Through a comprehensive literature review, this study analyzes various aspects of the interaction between AI and society, including ethical, social, economic, and psychological implications. The results of the study show that AI has great potential to improve efficiency, productivity, and quality of life for humans in various sectors. However, the adoption of AI also poses significant challenges related to privacy, security, social inequality, and job shifts. This study highlights the importance of a balanced and responsible approach in the development and implementation of AI, taking into account ethical and humanitarian aspects. The implications of this study are relevant for policymakers, industry players, and the general public in facing the AI ​​era.